Analysis of the Integration Process of Vulnarable Communities in Social and Economic Development: Batwa a Community of Muyange Site II - Ndabarushimana, Alexis; Ndayizeye, Desire (European Scientific Journal, ESJ, 2023)
The lack of access to food, to education, to house, to medical health care, to freedom of participation and the lack of access to sanitary facilities are some of the characteristics of the person who is qualified to be vulnerable. Vulnerability may arise from individual, community, or larger population challenges and requires different types of policy interventions from social and economic development of neighborhoods and communities and income policies, to individual medical intervention. Therefore, the purpose of this study is to analyze the integration process of vulnerable communities in social and economic development, case study of Batwa community of Muyange site II. The objectives of this study are (1), to identify the living conditions of Batwa communities as vulnerable people in Muyange Site II, (2) to show the factors that are hampering the integration process of Batwa communities in social and economic development in Muyange Site II, (3) to find out the role of local administration in the integration process of vulnerable communities in social and economic development, (4) to come up with practical solutions which can accelerate the integration process of Batwa communities in social and economic development. Through stratified random sampling technic, the research obtained a sample size of 50 households for the study. Therefore, this study combined both qualitative method and quantitative method with the use of the interview guide for qualitative approaches and quantitative with the use of a questionnaire administered directly to Batwa community from Muyange site II. The study established that Batwa community of Muyange Site II faced the problems that hampered the integration process in social and economic development like the lack of access to food, to plots for agricultural basic activities, to education and living in extreme poverty. The study again established that Batwa communities of Muyange Site II are not unique. The study also established that there are different causes that hampered the integration process and set strategies to be adopted by Batwa communities, local administration and the government in order to accelerate this integration process of vulnerable. Moreover, the study found out that Batwa communities should esteem themselves strong and responsible when maintaining the materials of the woodwork and learn how to do the small business in order to be self-financed instead of going out to beg. The study found out again that the local administration should give hope for a positive and improved change in the integration process and that the government should handle Batwa community issues as barriers for the social and economic development and help vulnerable to own houses and land. This will help vulnerable to overcome all kinds of discrimination in social and economic integration process.